Effects of Elevated CO2 on Photosynthetic Accumulation, Sucrose Metabolism-Related Enzymes, and Genes Identification in Goji Berry (Lycium barbarum L.) - Ma, Yaping; Xie, Yun; Ha, Rong; Cao, Bing; Song, Lihua (Frontiers in Plant Science, 2021)
Goji berry (Lycium barbarum L.) exposure to elevated CO2 (eCO2) for long periods reduces their sugar and secondary metabolite contents. However, sugar accumulation in fruit depends on photosynthesis and photoassimilate partitioning. This study aimed to explore photosynthesis, sugar content, and sucrose metabolism-related enzyme activities in goji berry leaves and fruits under ambient and eCO2 levels, and identify the genes encoding L. barbarum acid invertase (LBAI), L. barbarum sucrose synthase (LBSS), L. barbarum sucrose phosphate synthase (LBSPS), and L. barbarum neutral invertase (LBNI), based on transcriptome profiling. Further, the characterization of four identified genes was analyzed including subcellular localization and expression patterns. In plants grown under eCO2 for 90 or 120 days, the expression of the above-mentioned genes changed significantly as the photosynthetic rate increased. In addition, leaf and fruit sugar contents decreased, and the activities of four sucrose metabolism-related enzymes increased in leaves, while acid and neutral invertase increased in fruits. Protein sequence analysis demonstrated that LBAI and LBNI contain a conservative structure domain belonging to the glycosyl hydrolases (Glyco_hydro) family, and both LBSS and LBSPS belonging to the sucrose synthase (Sucrose_synth) and glycosyltransferase (Glycos_transf) family. Subcellular localization analysis showed that LBAI, LBNI, and LBSS were all located in the nucleus, plasma membrane, and cytoplasm, while LBSPS was located in the plasma membrane. The expressions of LBAI, LBSPS, and LBNI were high in the stems, whereas LBSS was predominantly expressed in the fruits. Our findings provide fundamental data on photosynthesis and sugar accumulation trends in goji berries under eCO2 exposure.